ANALISIS LAPORAN KEUANGAN SEBAGAI ALAT MENILAI KINERJA KEUANGAN PERUSAHAAN PADA PT MILDA BONTANG - Budyansa; Akhmadiansyah (I-Con Media, 2022)
PT. MILDA Bontang is a company engaged in the construction sector having its address at Jl. RT port. 10 No. 42 Ex. Tj Laut Indah which has 50 permanent employees in Bontang with President Director Mr. Amalianto. This research method uses horizontal analysis method. This type of research uses a descriptive approach that uses secondary data calculations obtained by the author from the company's annual financial statements for a period of two years, from 2018 to 2019, books and other sources. The purpose of this study was to determine the company's financial performance based on the level of liquidity, solvency, and profitability of PT MILDA in 2018-2019 and financial condition based on the financial statements of PT MILDA's performance in 2018-2019. The data collection method used is the library method, the observation method and the documentation method. The liquidity ratio means the company's financial position PT. MILDA Bontang from 2018 to 2019 is in a very good position (liquid) and Solvency in 2019 has increased compared to 2018 due to the percentage decrease in debt although capital has not changed and in the last two years PT. MILDA is still making a profit, this can be seen from the company's ability to generate profitability as indicated by positive ROA and ROE.